A standardized Physical Equivalent Temperature urban heat map at 1-m spatial resolution to facilitate climate stress tests in the Netherlands. (15th August 2020) - Koopmans, S.; Heusinkveld, B.G.; Steeneveld, G.J.
Abstract: In the Netherlands, municipalities and other sub-national governments have to conduct climate stress tests to examine the societal impact of heat load by citizens. So far, these parties have been hindered by the abundance of contrasting urban heat maps produced with different metrics and methods by different agencies. To unify the stress tests, we present a methodology for a standardized urban heat map at 1-m spatial resolution by selecting the Physical Equivalent Temperature (PET) as metric for heat stress. First we present an empirical regression model for PET, based on a variety of weather data and street configurations in the human thermal energy balance model Rayman. Thereafter, this empirical PET-model is evaluated for the midsized town Wageningen (the Netherlands). Meteorological observations taken at a nearby reference site and straightforward geographical data have been used as model input. Also, established methods were applied and elaborated to account for the urban heat island effect and wind speed reduction in the city. The presented method is validated against bike traverse observations of PET. Wind speed is the most challenging feature to map, due to its unsteady and local behaviour in cities. As a result, an afternoon averaged PET heat map is demonstrated as standard for an extreme heat day (1:1000 summer half year days), and a cumulative exceedance PET heat map for a representative year. Furthermore, a heat map is projected for 2050 according a warm climate change scenario. Highlights: Climate stress test in the Netherlands require standardized urban heat maps. Recipe to calculate Physiological Equivalent Temperature map on 1-m resolution. Heat map is based on GIS-based tools and empirical meteorological models. Validation with bicycle traverse observations in Wageningen (the Netherlands). Includes climatology heat maps with outlook for future climate scenario.